Computational investigation of drag reduction on an Ahmed Body using square grooves - Rawail Haseem (00000172079); Dr. Adeel Javed (USPCAS-E, NUST, Islamabad, 2020)
TH-220
Keywords: MS-TEE Thesis MS Thesis